FARMING RICE PRODUCTION EFFICIENCY ON FARMING STATUS BY LAND TENURE - Ratna Dewi; Mahludin Baruwadi; Amir Halid (State University of Gorontalo, 2019)
The study aims to determine (1) the factors that affect rice production in the district was. (2) Efficient use of land, seed, fertilizer, and labor on the fields in the district was. This research is quantitative. Sources of data in this research are secondary data from the primary data from questionnaires to farmers of paddy in Gorontalo. The data analysis technique used is the Cobb Douglas.These results indicate that (1) the results of the Cobb Douglas found that simultaneous land, seed, fertilizer, labor, and land tenure positive and significant impact on rice production in the district was the province of Gorontalo to the value of the determinant of 79,50% for tenants and owners of 67,50% to the tiller. Then the partial results only land, seed and labor are positive and significant impact on rice production in the district was Gorontalo province. The coefficient of land ownership that is positive indicates that farmers with its status as the owner of tenants is better than the sharecroppers in generating optimal production. (2) The results of the technical efficiency analysis shows that the area of land, seed, labor, and land tenure have a greater value than one that is in the category yet efficient (increasing returns to scale). Then for fertilizer has a smaller value than one that is in the category inefficient (decreasing return to scale). The results of the comparison in terms of the land status was found that the owner of tenants is better than the tenants in the efficiency of production input rice production in the district was.